TRANSFORMASI SOSIAL DAN IDENTITAS DI ERA AI: KAJIAN POSTHUMANISME DALAM NOVEL MENANAM GAMANG - Murahim Murahim; Mahmudi Efendi; Farida Jaeka; Karoluslina Karoluslina; Wahida Apriani (Universitas Nahdlatul Wathan Mataram, 2026)
The novel Menanam Gamang by Dhianita Kusuma Pertiwi reflects a post-pandemic world dominated by technology and artificial intelligence (AI) in human life. Set two decades after a global pandemic, the novel depicts humanity’s uncertainty in facing both the comfort and the existential void brought about by dependence on technology. This study aims to examine how social transformation and human identity are represented in the novel using a posthumanism theoretical approach. The method employed is qualitative research based on literary text analysis, focusing on narratives, dialogues, and descriptions related to the relationship between humans and technology. The findings reveal that technology in the novel functions not merely as a tool but has transformed into an entity that reshapes the way humans think, feel, and interact. Human identity becomes fluid, social relations undergo disruption, and traditional values are marginalized. These findings suggest that literature can serve as a reflective space for understanding the dilemmas of humanity amidst the relentless tide of technology. Keywords: Posthumanism; Identity; AI; Novel; Technology.